Situation Report: Romania, 16 September 1970 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Ceausescu-Zhivkov Summit Meeting Serbian Premier Visits Romania Delegation to UN General Assembly Named Economic Agreements with the Soviet Union